Aging-dependent immunological changes in multiple sclerosis - Iribarren-López, Andrea; Martins-Almeida, Laura; Wells, Jadon K; Castillo-Triviño, Tamara; Prada, Álvaro; Pickett, Hilda A; Alberro, Ainhoa; Otaegui, David (Frontiers in Immunology, 2025)
Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative disease in which immune dysregulation plays a central role. As the life expectancy of people with MS (pwMS) increases, understanding how aging affects their immune system—collectively referred to as immunosenescence—has become crucial. In this study, we characterized immunosenescence in pwMS by analyzing age-related changes in the immune system. To fulfill this, blood samples were collected from pwMS and healthy controls (HCs) of independent cohorts: i) immune cell populations were assessed in PBMCs (n= 110), ii) thymic involution and telomere attrition were measured in DNA samples (n=150), and iii) inflammatory and neurodegeneration markers were evaluated in plasma (n=146).Our results revealed distinct age-associated alterations in immune cell subsets between pwMS and HCs, including B and NK cells. Notably, pwMS showed an age-related increase in CD28–CD57+ and CD28+CD57+ cells in CD4+ and CD8+ T cells. Thymic involution was reported with age in both groups and, importantly, we found a more pronounced thymic involution in younger pwMS. A positive correlation was found between age and the levels of IL-6, TNF-α, and CRP in pwMS, results consistent with the inflammaging phenomenon. Similarly, NFL levels were elevated in pwMS and correlated positively with age in both groups., Remarkably, we found a positive correlation between NFL levels and IL-6, and between NFL levels and TNF-α only in pwMS. Telomere shortening occurred with age in both groups, without significant differences. Notably, our study provides an integrative and multi-biomarker characterization of immune aging process in pwMS, revealing new insights into this complex relationship. These findings highlight specific age-related immune alterations in MS and underscore the importance of incorporating age and immunosenescence monitoring into MS clinical management and therapeutic strategies.